Effects of supplementation of medium with different antioxidants during in vitro maturation of bovine oocytes on subsequent embryo production - Sovernigo, TC; Adona, PR; Monzani, PS; Guemra, S; Barros, FDA; Lopes, FG; Leal, CLV (Reproduction in domestic animals, 2017)
Contents The aim of this study was to assess the effects of different antioxidants on the levels of reactive oxygen species (ROS) and glutathione (GSH) in oocytes during in vitro maturation (IVM), as well as on the production of embryos. Oocyte of slaughterhouse‐derived cattle ovaries were placed in IVM with different antioxidants: quercetin (2 μM), cysteamine (100 μM), carnitine (0.5 mg/ml), vitamin C (50 μg/ml) or resveratrol (2 μM). Oocytes matured without any antioxidant supplementation were used as control. The oocytes were assessed for maturation rates and for ROS and GSH levels by fluorescence staining in 2′,7′‐dichlorodihydrofluorescein diacetate and Cell Tracker Blue, respectively. Embryo production was assessed in terms of cleavage, blastocysts and hatching rates and embryo cell numbers. The results expressed in arbitrary fluorescence units showed ROS reduction (p < .05) in the groups with quercetin (27.5 ± 3.4), vitamin C (27.1 ± 3.0) or resveratrol (28.1 ± 4.7), in comparison with those with cysteamine (34.9 ± 4.5), carnitine (34.6 ± 3.8) or to the control group (36.5 ± 5.2). GSH levels increased (p < .05) in cysteamine (63.5 ± 5.5) or carnitine (60.8 ± 4.4) groups in comparison with quercetin (52.7 ± 5.1), vitamin C (53.0 ± 3.8), resveratrol (53.1 ± 4.4) or to the control (49.6 ± 4.5). Nuclear maturation cleavage and hatched blastocysts rates did not differ (p > .05) between groups. However, blastocyst rates after in vitro fertilization in quercetin (53.5 ± 3.9%), vitamin C (52.1 ± 3.1%) resveratrol (54.2 ± 4.0%), cysteamine (52.4 ± 2.7%) or carnitine (54.2 ± 3.1%) groups were higher (p < .05) than in the control (47.2 ± 2.7%). Total cell numbers in embryos from the vitamin C, resveratrol, cysteamine or carnitine groups were higher than in quercetin and control groups, which were similar to each other. The results suggest that using antioxidants during IVM may reduce oxidative stress either by decreasing ROS levels directly or by increasing GSH levels in oocytes, depending on the type of antioxidant used. Overall, oxidative stress control during IVM with the antioxidants examined here improved blastocyst development with similar efficacy.